Establishing the Strength Characteristics of the Lifting-Leveling Device Structures of the VPO-3-3000 Machines for the Track Straightening - Adil Kadyrov; Akbope Karsakov; Bakytzhan Donenbayev; Kyrmyzy Balabekova (Communications - Scientific letters of the University of Zilina, 2020)
This article deals with replacement of the magnetic grippers on the VPO-3-3000 machines with roller grippers. The novelty lies in establishment of dependences characterizing stress and strain in elements of the lifting and straightening devices and in rails during the operation. Reliability of the program for calculating the structural parameters of the lifting and straightening device for the VPO-3-3000 track renewal machine is shown. The developed design of the lifting and straightening device makes it possible to select the rational parameters of technology and the operating mode of the device. This design is recommended for use when developing working bodies for the straightening machines. The article presents calculation of the lifting and straightening device structural elements’ strength during operation, in the Ansys WB software package.